The effect of the fan card strategy on the performance of some offensive handball skills for female students - Hussein, Prof. Dr. Zardasht Muhammad Rauf; Student, Hazh Abdul Rahman / Master's (Sulaimani Journal for Humanities, 2026)
The introduction to this research and its significance: The teaching process is a continuous series of relationships that develop between the teacher, the student, and the curriculum. These relationships help the student develop as an individual or as a participant in a specific activity or event, acquiring a certain level of skill in physical activities. The world today has become a global village where the interests of nations and peoples are intertwined and overlapping. Science has become the hallmark of our time and a tool for development and progress, as well as for raising generations on a scientific approach to thinking. This is especially true since one of the most important goals of education is to develop the human mind by providing it with accurate information and sound mental and intellectual habits. Therefore, it is certain that education plays a major role in shaping the individual by promoting all aspects of their potential for growth. It is a planned and organized process that aims to help the individual achieve healthy and integrated development in physical, mental, emotional, and social aspects, enabling them to adapt to themselves and their surroundings. This study aimed to identify the impact of the fan card strategy on the performance of some offensive handball skills among the research sample. The research aims to identify the differences between the experimental and control groups in the performance of some offensive handball skills among the research sample. In post-tests, the research procedures were defined as the research population being the second-year students in the Department of Basic Education at the College of Physical Education and Sports Sciences, University of Sulaimani, for the academic year (2024-2025), totaling (115) students, with (82) male students and (33) female students. Male students were excluded from the research sample because the researcher is conducting her research on female students only, distributed across three study sections. (12) female students were randomly selected from section (A) for the experimental group, and (12) female students were randomly selected from section (B) for the control group. Thus, the sample percentage to the original population reached 28.69%. For the purpose of equivalence, the students who practiced and did not adhere to attendance and who participated in the pilot study were excluded. Then, the equivalence of the two research groups in handball skills was carried out. The researcher concluded the following: The use of the fan-card strategy proved effective in teaching handball skills (speed of passing against the wall, continuous dribbling, and shooting accuracy) to the experimental group in the research sample, as demonstrated by the pre- and post-tests. The use of the fan-card strategy proved effective in teaching handball skills (speed of passing against the wall and shooting accuracy) to the experimental group in the research sample, as demonstrated by the post-tests. The use of the traditional method proved effective in teaching continuous dribbling to the control group, as demonstrated by the post-tests. The use of the traditional method proved effective in teaching continuous dribbling to the control group, as demonstrated by the pre- and post-tests.